Prevalence of Human Immunodeficiency Virus and Sexually Transmitted Infections Among Cisgender and Transgender Women Sex Workers in Greater Kuala Lumpur, Malaysia - Wickersham, Jeffrey A.; Gibson, Britton A.; Bazazi, Alexander R.; Pillai, Veena; Pedersen, Courtney J.; Meyer, Jaimie P.; El-Bassel, Nabila; Mayer, Kenneth H.; Kamarulzaman, Adeeba; Altice, Frederick L. (Lippincott, Williams & Wilkins, 2017)
Background Sex workers face a disproportionate burden of human immunodeficiency virus (HIV) and sexually transmitted infections (STI) worldwide. For cisgender women sex workers (CWSW), global HIV prevalence is over 10%, whereas transgender women sex workers (TWSW) face an HIV burden of 19% to 27%. Methods We used respondent-driven sampling to recruit 492 sex workers, including CWSW (n = 299) and TWSW (n = 193) in Greater Kuala Lumpur, Malaysia. Participants completed an in-depth survey and were screened for HIV, syphilis, Chlamydia trachomatis, and Neisseria gonorrhoeae. Sample characteristics stratified by gender identity and interview site are presented. Bivariate analyses comparing CWSW and TWSW were conducted using independent samples t tests for continuous variables and χ 2 tests for categorical variables. Results Pooled HIV prevalence was high (11.7%; 95% confidence interval [CI], 8.8-14.5), and was similar for CWSW (11.1%) and TWSW (12.4%). Rates of syphilis 25.5% (95% CI, 21.6-29.5), C. trachomatis (14.8%; 95% CI, 11.6-18.0) and N. gonorrhoeae (5.8%; 95% CI, 3.7-7.9) were also concerning. Both groups reported lifetime HIV testing (62.4%), but CWSW were less likely to have ever been HIV tested (54.5%) than TWSW (74.6%). Median time since last HIV test was 24 months. Previous screening for STI was low. Inconsistent condom use and drug use during sex work were not uncommon. Conclusions High HIV and STI prevalence, coupled with infrequent HIV and STI screening, inconsistent condom use, and occupational drug use, underscore the need for expanded HIV and STI prevention, screening, and treatment efforts among CWSW and TWSW in Malaysia.